An active routing prefix caching algorithm for IP address lookup - Guo-sheng Zhu; Shao-hua Yu; Jin-you Dai (2009 Fourth International Conference on Communications and Networking in China, 2009)
A lot of IP address lookup algorithms have been widely studied. Among them we have thorough investigated the caching based algorithms. It is based on the locality assumption of Intenet traffic which is questionable especially in high speed backbone. There is enough locality if routing prefixes are cached instead of individual IP addresses. However the previous prefix caching scheme need to do complete or partial prefix expansion to cache corresponding prefix which will lead to prefix table explosion and make incremental updates difficult. A new active prefix caching algorithm based on prefixes covering relationship is proposed in this paper. Incremental updates are supported without prefix expansion. Performance evaluation shows our proposed scheme has higher cache hit rate, less memory space than previous schemes.